2005
DOI: 10.1073/pnas.0505288102
|View full text |Cite
|
Sign up to set email alerts
|

The tethered motor domain of a kinesin-microtubule complex catalyzes reversible synthesis of bound ATP

Abstract: Although the steps for the forward reaction of ATP hydrolysis by the motor protein kinesin have been studied extensively, the rates for the reverse reactions and thus the energy changes at each step are not as well defined. Oxygen isotopic exchange between water and P i was used to evaluate the reverse rates. The fraction of the kinesin⅐ADP⅐P i complex that reverts to ATP before release of Pi during net hydrolysis was Ϸ0 and Ϸ2.6% in the absence and presence of microtubules (MTs), respectively. The rate of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 29 publications
8
90
1
Order By: Relevance
“…Yet important questions remain. Does processive backward stepping synthesize ATP -a true cycle reversal as detected by Hackney et al [42]? Is ATP hydrolysis required?…”
Section: Kinesin Processivity: Unresolved Questionsmentioning
confidence: 94%
See 2 more Smart Citations
“…Yet important questions remain. Does processive backward stepping synthesize ATP -a true cycle reversal as detected by Hackney et al [42]? Is ATP hydrolysis required?…”
Section: Kinesin Processivity: Unresolved Questionsmentioning
confidence: 94%
“…One point of controversy is the position of the tethered head with respect to the bound head and microtubule lattice. Recent biochemical experiments have indicated that the rear ADP-containing head of kinesin (steps K1 and K6-K7) can infrequently synthesize ATP, suggesting that tight microtubule binding occurs, at least transiently [42]. However, because ATP resynthesis is energetically costly and inhibits processivity, it is possible that entry into the synthesis-competent state is also strain-regulated, limiting the probability of ATP resynthesis, which is measured to be <3% [42].…”
Section: Kinesin Processivity: Unresolved Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinesin motor exhibits tight coupling, i.e., it hydrolyzes one ATP molecule per mechanical step [10]. After ATP has been hydrolyzed by one of the catalytic motor domains (or active sites), the inorganic phosphate is released rather fast, and both transitions together take of the order of 10 ms to be completed [11]. ADP is subsequently released from the catalytic domain, and this release process is also completed during about 10 ms [12].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the extensive single-molecule studies, how kinesin functions to generate the force for discrete translation on a single protofilament of the microtubule is not well understood, leaving many questions on, for instance, substeps, backsteps, and fraction of power stroke and diffusion to each step [10,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%